PEER ASSESSMENT IN PUBLIC SPEAKING: PERCEPTIONS, PRACTICES, AND REFLECTIONS OF PRE-SERVICE ENGLISH TEACHERS - Zainul Aminin; Munir, Ahmad; Leliana, Ayunita (STKIP Siliwangi, 2025)
This study aims to investigate the perceptions, practices and reflections of pre-service English teacher towards peer assessment in Public Speaking course. This study not only focuses on students' perceptions, but also discusses how students practice this peer assessment and how they reflect on the implementation of this peer assessment. A basic interpretative study approach was used because it focuses on understanding the meaning individuals ascribe to their experiences. This approach allows researchers to explore the complexities of peer assessment from the participants' perspectives, rather than simply measuring outcomes. The participants in this study were 26 second-semester students from the 2023 intake of the English Language Education Program, who were enrolled in the Public Speaking course. There were three instruments needed to collect data, namely open-ended questionnaire, observation and peer assessment rubric. The findings reveal that most students positively perceive peer assessment as an effective tool for receiving feedback and improving their speaking skills. In practice, students utilized the rubric to evaluate their peers, providing scores, identifying strengths and weaknesses, and presenting feedback. Reflecting on these experiences, some students suggested that the peer assessment rubric could be simplified to enhance clarity and better align with the course objectives.